Implementation of lean process to solid waste management in Bandung, Indonesia - Joval Ifghaniyafi Farras; Sarasi, Vita; Chaerudin, Iman; Primiana, Ina; Yunani, Akhmad (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Household waste in Bandung City is one of the problems due to the increase in waste generated by the community from year to year and the limited land or Final Disposal Site (TPA) in Bandung City. The land capacity at the Final Disposal Site of Sarimukti decreases every year and the waste generation reaches 9 meters. This happens because there is no effective and efficient waste management technology. To overcome this waste generation, this research was carried out which aims to find out how the current household waste is processed, identifying lean operations of zero waste management processing, perform a zero waste management technology simulation using a dynamic system, comparing the total costs required with the total benefits received when using zero waste management technology, and designing a lean canvas business model for the processing of zero waste management. This study uses a cost benefit analysis method with a System Dynamics approach in conducting model simulations and designing a lean canvas business model for zero waste management. The results of the study consist of three scenarios, namely pessimistic, most likely and optimisticic scenarios, each scenario shows that Bandung City can achieve zero waste conditions in the fifth year for the most likely scenario and the fourth year for the optimisticic scenario except for the pessimistic scenario. Benefit Cost Ratio value for pessimistic scenario is 0.660, Most Likely scenario is 0.767, optimisticic scenario is 1.172. This method allows the occurrence of lean operations in waste management which are shown by flowcharts and process graphs by eliminating activities that do not have added value. Furthermore, to support the operations of this research, a recommendation is made in the form of lean operations using 5S on household waste sorting behavior and the preparation of a lean canvas business model so that the implementation of Zero Waste Management is optimal